1994
DOI: 10.1016/0014-5793(94)80214-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and biological activity of a novel antibacterial peptide deduced from a pig myeloid cDNA

Abstract: Several myeloid precursors of antibacterial peptides have recently been shown to share homologous pre-and pro-regions. Taking advantage of this homology, a novel cDNA was cloned from pig bone marrow RNA. This encodes a 166-residue polypeptide with highly conserved pre-(29 residues) and pro-(101 residues) sequences, followed by a unique, 36-residue C-terminal sequence. Structure analyses of this C-terminal region have identified a highly cationic sequence predicted to adopt an amphipathic a-helical conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 23 publications
(3 reference statements)
3
102
0
Order By: Relevance
“…Peptides corresponding to all known sequences have either been purified from natural sources [13,[34][35][36][37][38][39], after processing of the respective precursors, or have been obtained by chemical synthesis based on the sequence deduced from cDNA [26,27,29,32,33]. At present they include rabbit CAPI8(106 142) [39], human FALL-39/CAP18 [32,33], PMAP-36 [26] and PMAP-37 [29], all of which are mostly s-helical; two Trpcontaining peptides, indolicidin [36] and PMAP-23 [27]; the Pro-and Arg-rich Bac5 [12], Bac7 [12], PR-39 [13] and prophenin [38]; the cyclic dodecapeptide [34] and protegrins [37] which are loop-forming molecules with one and two disulfide bonds, respectively. The sequence of the Pro-and Arg-rich peptides (Fig.…”
Section: Structure and Function Of The Mature C-terminal Peptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Peptides corresponding to all known sequences have either been purified from natural sources [13,[34][35][36][37][38][39], after processing of the respective precursors, or have been obtained by chemical synthesis based on the sequence deduced from cDNA [26,27,29,32,33]. At present they include rabbit CAPI8(106 142) [39], human FALL-39/CAP18 [32,33], PMAP-36 [26] and PMAP-37 [29], all of which are mostly s-helical; two Trpcontaining peptides, indolicidin [36] and PMAP-23 [27]; the Pro-and Arg-rich Bac5 [12], Bac7 [12], PR-39 [13] and prophenin [38]; the cyclic dodecapeptide [34] and protegrins [37] which are loop-forming molecules with one and two disulfide bonds, respectively. The sequence of the Pro-and Arg-rich peptides (Fig.…”
Section: Structure and Function Of The Mature C-terminal Peptidesmentioning
confidence: 99%
“…1) is peculiar in that several short modules are present, and often arranged in tandem repeats [12,13,38]. The structure of some of these peptides has been analyzed by circular dichroism spectroscopy, showing that PMAP-36 [26], PMAP-37 [29] and FALL-39 [32] undergo a transition from a random coil to an ordered, mainly s-helical conformation on addition of an organic solvent. This behaviour indicates the presence of an amphipathic s-helical conformation, a structure found in many membrane-active peptides.…”
Section: Structure and Function Of The Mature C-terminal Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…PR-39 was isolated originally from bulk homogenates of porcine small intestines [2] but further studies demonstrated that this cathelicidin was derived from neutrophils and not from intestinal epithelia [68]. PR-39 is active mainly against gram-negative bacteria [2,63] and increases significantly in pig sera during the onset of salmonellosis [76].…”
Section: Role Of Iec In the Secretion Of Defensins And Other Antibactmentioning
confidence: 99%